FRI0161 Role of gitr/gitrl in modulating th9 response in psoriatic arthritis. (12th June 2018) - Guggino, G.; di liberto, D.; Rizzo, A.; La Manna, M.; Ferrante, A.; saieva, L.; Alessandro, R.; Sireci, G.; ciccia, F.
Abstract : Background: GITR/GITRL interaction is pivotal in regulating the activity of Treg and of Th9 effector cells. 1 Psoriatic arthritis (PsA) is a chronic inflammatory disease characterised by a strong expression of IL-9 and Th9 polarisation in the inflamed gut, synovial tissues and peripheral blood. 2 Factors involved in the regulation of Th9 responses in PsA have been not yet investigated. Objectives: Aim of the study: to investigate the role of GITR/GITRL in PsA. Methods: GITR, GITRL expression were assessed by rt-PCR and immunohistochemistry in synovial biopsies, gut specimens and bone marrow of PsA patients and healthy controls (HC). The co-localization of CD4 and GITR was analysed by immunofluorescence. The expression of GITR was also assessed by flow cytometry analysis in isolated PBMC of patients and controls (Tregs, CD4 and CD8). Peripheral and intestinal IL-9 producing cell (Th9) percentages and cytotoxic activity of T lymphocytes were also studied by flow cytometry analysis ex vivo and after in vitro stimulation with GITRL. A mouse model of induced arthritis (collagen induced arthritis, CIA) was used to study GITR/GITRL axis and the effect of anti-GITRL blocking agent. Results: Increased GITR and GITRL expression was observed in the inflamed gut and synovial samples of PsA patients. Analysis of GITR expression among PBMC and LPMC from PsA patients demonstrated its down-regulation among Tregs and upregulation on effector CD4 +and CD8+T cells. In in vitro studies, GITR co-stimulation potently induced Th9 activation and IL-9 production. In particular, GITR ligation subverted the induction of Foxp3(+) Tregs, directing the activated CD4(+) T cells to a Th9 phenotype and enhancing the function of DCs and cytotoxic T lymphocytes. Moreover, in a murine model of CIA massive expression of IL-9 and GITR was observed in the synovial tissues and anti-GITR therapy significantly ameliorated arthritis score. Conclusions: We demonstrated that GITR/GITRL axis modulates IL-9/Th9 responses in PsA, representing GITR activation a relevant upstream pathway involved in Th9 polarisation. A novel mechanism by which GITR agonist exert an inflammatory response was also demonstrated in PsA indicating GITR blocking agents as possible therapy in PsA. References: [1] Xiao X, Shi X, Fan Y, Zhang X, Wu M, Lan P, Minze L, Fu YX, Ghobrial RM, Liu W, Li XC. GITR subverts Foxp3(+) Tregs to boost Th9 immunity through regulation of histone acetylation. Nat Commun. 2015Sep 14;6:8266. [2] Ciccia F, Guggino G, Ferrante A, Raimondo S, Bignone R, Rodolico V, Peralta S, Van Tok M, Cannizzaro A, Schinocca C, Ruscitti P, Cipriani P, Giacomelli R, Alessandro R, Dieli F, Rizzo A, Baeten D, Triolo G. Interleukin-9 Overexpression and Th9 Polarization Characterize the Inflamed Gut, the Synovial Tissue, and the Peripheral Blood of Patients With Psoriatic Arthritis. Arthritis Rheumatol2016Aug;68(8):1922–31. [3] Xiao X, et al. GITR subverts Foxp3(+) Tregs to boost Th9 immunity through regulation of histone acetylation. Nat Commun. 2015Sep. [4] Ciccia F, Guggino G, et al. Interleukin-9 Overexpression and Th9 Polarization Characterize the Inflamed Gut, the Synovial Tissue, and the Peripheral Blood of Patients With Psoriatic Arthritis. Arthritis Rheumatol 2016Aug. Disclosure of Interest: None declared